2009
DOI: 10.1097/ede.0b013e3181b09332
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Use of Written Japanese and Protection From Late Life Dementia

Abstract: Background The cognitive reserve hypothesis would predict that use of written Japanese should confer protection against dementia because of the complexity of its ideograms compared with written English. We sought to test this hypothesis in analyses from a longitudinal study of Japanese-American men. Methods Participants were second-generation Japanese-American men (Nisei) on the island of Oahu, Hawaii, who were seen in 1965 and in subsequent examinations to detect dementia beginning in 1991-1993. Use of spok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 26 publications
4
44
1
1
Order By: Relevance
“…This discrepancy might be caused by the self-reported and less accurate questionnaire about physical activities we utilized. Hypertension, type 2 diabetes, smoking, and urban living environment were not correlated with age at AD onset, which is similar to the results of other studies [5, 7, 23, 24]. …”
Section: Discussionsupporting
confidence: 82%
“…This discrepancy might be caused by the self-reported and less accurate questionnaire about physical activities we utilized. Hypertension, type 2 diabetes, smoking, and urban living environment were not correlated with age at AD onset, which is similar to the results of other studies [5, 7, 23, 24]. …”
Section: Discussionsupporting
confidence: 82%
“…While some researchers do not support this potential consequence of bilingualism when the characteristics of the samples are carefully controlled for (see Chertkow et al, 2010;Lawton et al, 2015), others report significant results even in carefully matched groups (see Alladi et al, 2013;Woumans et al, 2015). However, as correctly stated by Paap et al (2015b), the most compelling pieces of evidence at this regard may come from longitudinal studies following cohorts of individuals, and most of these studies yielded non-significant differences, or even monolingualfavoring trends (e.g., Crane et al, 2009;Lawton et al, 2015;Sanders et al, 2012;Yeung, St. John, Menec, & Tyas, 2014;Zahodne et al, 2014), while only one presented evidence in favor of a bilingual advantage at this level of analysis (Wilson, Boyle, Yang, James, & Bennett, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…As a potential solution for the conundrum presented by the unclear debate of the role of bilingualism in patients with dementia, a handful of studies have opted for a longitudinal approach, testing cohorts starting from a baseline stage in which no signs of dementia are evident. Most of the studies using this approach have shown no consistent delay in the onset of the symptoms caused by bilingualism (Crane et al, 2009;Lawton, Gasquoine, & Weimer, 2015;Sanders, Hall, Katz, & Lipton, 2012;Yeung, St. John, Menec, & Tyas, 2014;Zahodne, Schofield, Farrell, Stern, & Manly, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Yet, they did not find bilingualism to delay onset of dementia even in the group with lower years of formal education. A strength of this study, as well as of the ones by Crane and colleagues (2009, 2010), is the fact that the data was longitudinal, which may reduce recall bias and also permits a more objective measure of incident dementia. Nevertheless, the authors acknowledged several limitations that might account for the findings.…”
Section: Bilingualism and Cognitive Reservementioning
confidence: 99%